Pengaruh Penggunaan Filler Abu Limbah Cangkang Kemiri Dalam Campuran Asphalt Concrete-Wearing Course (Ac-Wc) - SYAPUTRA, M TAUFIK AKBAR (Civil Infrastructure Engineering and Architectural Design, 2025)
The use of environmentally friendly materials in road construction has received increasing attention, particularly in efforts to utilize waste as a value-added additive. One potential organic waste is candlenut shell ash, which contains specific chemical compounds that may affect the characteristics of asphalt mixtures. This study aims to investigate the effect of adding candlenut shell ash on the mechanical properties of Asphalt Concrete–Wearing Course (AC-WC) mixtures. The research method employed is a laboratory experiment with variations of candlenut shell ash content at 4%, 6%, 8%, and 10% of the total filler weight. Testing was conducted using the Marshall method to obtain values of stability, flow, Marshall Quotient (MQ), as well as VIM, VMA, and VFA.The Marshall test results indicate that the addition of candlenut shell ash influences the Marshall characteristics of AC-WC mixtures. At certain levels, the ash improves stability and flow values, demonstrating enhanced strength and stiffness of the mixture. However, at excessively high levels, the mixture performance declines. The optimal condition was achieved with 6% ash content, which yielded the highest stability and MQ values while meeting the 2018 Bina Marga specifications. Therefore, candlenut shell ash has the potential to be used as an additive in AC-WC mixtures, while also serving as an environmentally friendly waste management solution.